Respuesta :

Answer:

2

Step-by-step explanation:

√3x=√3+√3=2√3⇒x=2

[tex]\implies {\blue {\boxed {\boxed {\purple {\sf { \: x = 2}}}}}}[/tex]

[tex]\large\mathfrak{{\pmb{\underline{\red{Step-by-step\:explanation}}{\red{:}}}}}[/tex]

[tex] \sqrt{3} x - \sqrt{3} = \sqrt{3} [/tex]

➺ [tex] \: \sqrt{3} x = \sqrt{3} + \sqrt{3} [/tex]

➺ [tex] \: \sqrt{3} x = 2 \sqrt{3} [/tex]

➺ [tex] \: x = \frac{2 \sqrt{3} }{ \sqrt{3} } [/tex]

➺ [tex] \: x = 2[/tex]

[tex]\bold{ \green{ \star{ \orange{Mystique35☂}}}}⋆[/tex]

ACCESS MORE